Strategic control of excess tellurium to achieve high figure-of-merit in Te-rich Bi0.5Sb1.5Te3 - Ranu Bhatt; Rishikesh Kumar; Pramod Bhatt; Pankaj Patro; Shovit Bhattacharya; Mani Navaneethan; Soumen Samanta; Ajay Singh (Materials for Renewable and Sustainable Energy)
Abstract Increasing the Te content in stoichiometric Bi0.5Sb1.5Te3 facilitates effective control over the anti-site defects and nanostructure; however, arresting excess Te in the host matrix is challenging. Herein, we report the success of a saturation-annealing treatment in a vacuum, followed by air-quenching as a promising approach for synthesizing high figure-of-merit (zT) Bi0.5Sb1.5Te3+xTe (x = 0, 2, 5 and 10 wt%) materials. A remarkably high-power factor (α 2 σ ~ 6 mW at 300 K) is achieved in p-type Bi0.5Sb1.5Te3 + 5 wt% Te composition due to high carrier concentration (n) and good carrier mobility (µ). Microstructural analysis revealed the formation of densely interconnected polycrystalline grains featuring fine grain boundaries, planar/point defects, and strain field domains, contributing towards wide-length scale phonon scattering. The cumulative effect of drastically reduced thermal conductivity (κ ~ 0.8 W/m-K at 300 K), and enhanced power factor resulted in a record zT value ~ 2.2 at 300 K in Bi0.5Sb1.5Te3 + 5 wt% Te, with an average zT value up to 1.35 in temperatures ranging from 303 to 573 K. The COMSOL simulations predict a maximum conversion efficiency (η max ) of ~ 15%, at a temperature gradient (∆T) of 270 K, for a single-leg thermoelectric generator (TEG) developed using this material.